Estimation of crown characters and leaf biomass from leaf litter in a Malaysian canopy species, Elateriospermum tapos (Euphorbiaceae) - Osada, Noriyuki; Takeda, Hiroshi; Kawaguchi, Hideyuki; Furukawa, Akio; Awang, Muhamad (Elsevier, 2003)
We estimated crown characteristics, such as median crown height, leaf fall rate and leaf biomass, from litter leaves for a Malaysian canopy species, Elateriospermum tapos. Leaf morphology was compared between the harvested and litter leaves for trees of various heights. Also, litter traps were set systematically around the trees of various heights, and distribution patterns were investigated for litter leaves. Leaf area and dry weight decreased with increasing height in a similar manner in both leaf litter and harvested leaves. This suggests that median crown height can be estimated from mean area or mass of the leaf litter of a tree in this species. Furthermore, horizontal distribution patterns of litter leaves were well explained by the Gaussian kernel. Leaf fall rate was estimated to be 2.0-28.1 kg per tree per year in the five trees of various heights, and was greater in taller trees. Since leaf life span was smaller for taller trees, leaf biomass was estimated to be 2.6-30.5 kg per tree, and was also greater in taller trees. These estimated values are similar to the values estimated from the allometric equation that uses the diameter at breast height and overall tree height as parameters.